Frailty in elderly patients undergoing primary percutaneous coronary intervention. (February 2019) - Calvo, Elena; Teruel, Luis; Rosenfeld, Laia; Guerrero, Carmen; Romero, Marta; Romaguera, Rafael; Izquierdo, Silvia; Asensio, Susana; Andreu-Periz, Lola; Gómez-Hospital, Joan Antoni; Ariza-Solé, Albert
Background: The prevalence of frailty, cognitive impairment and disability and its prognostic impact in patients with myocardial infarction undergoing primary percutaneous coronary intervention is unknown. Aims: The aim of this study was to assess the prevalence of frailty and other ageing-related variables and their association with inhospital mortality in consecutive elderly ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention in a tertiary care hospital. Methods: We prospectively included patients aged 75 years or older with STEMI undergoing primary percutaneous coronary intervention. The nursing team provided pre-discharge, standardised questionnaires and tests to each patient to study the presence of frailty (FRAIL scale), comorbidity (Charlson index), disability (Barthel test, Lawton–Brody index), nutritional risk (MNA-SF test) and cognitive status (Pfeiffer test). The association between ageing-related variables and mortality was assessed by binary logistic regression. Results: A total of 259 patients were included with a mean age of 82.6±6 years, 57.9% men. A total of 51 patients (19.7%) were frail, 26 presented with moderate or severe disability (10%), and 82 were at risk of malnutrition (31.7%). Frailty was associated with a higher prevalence of diabetes, hypertension and previous stroke, and a higher inhospital mortality (21.6% vs. 3.4%; P <0.001). After adjusting for potential confounders, this association remained significant (odds ratio 3.96; 95% confidence interval 1.16–13.56; P =0.028). Conclusion: A not negligible proportion of elderly patients with STEMI fulfilled the frailty criteria. Frailty was independently associated with mortality. A very simple, feasible geriatric assessment by trained nurses can contribute to predict mortality.